The Legacy of a Story: Commemoration and the Double-Narrative of Jeffrey Arenburg and Brian Smith - Walker, Jennifer (Disability Studies Quarterly, 2008)
This article examines a recent amendment to Ontario's mental health legislation that was named "in memory" of Brian Smith, a local television personality killed by Jeffrey Arenburg, a person diagnosed with a mental illness. Rather than evaluating the socio-legal validity of "Brian's Law", it critically attends to the emergent "narrative of commemoration" that helped consolidate collective memory of the event. The genesis of the legislation is traced through public documents that support the "storying" of the murder, inquest, and legislative debate, including the "mythologizing" of Smith and the derisive story of Arenburg. Both representations are essential to the social and political efficacy of this "double-narrative" and the formal process of commemoration. The "legacy" of Brian Smith as exemplar of moral and social responsibility depends upon the alternative public conception of Arenburg, as mentally ill and morally ambiguous. Essentially, this narrative reaches beyond individual experience, and even social memory, and becomes enshrined in law as institutional memory.